The good women of the parish : gender and religion after the Black Death - French, Katherine L. (Philadelphia, Pa. : University of Pennsylvania Press, 2008)
French argues that medieval laywomen both coped with the chaotic changes following the plague and justified their own changing behavior by participating in local religion. Through active engagement in the parish church, the basic unit of public worship, women promoted and validated their own interests and responsibilities.
"My wedding gown to make a vestment": housekeeping and churchkeeping -- Hatched, matched, and dispatched: life cycles and the liturgy -- "My pew in the middle aisle": women at mass -- Maidens' lights and wives' stores: women's parish groups -- "To save them from binding on hock Tuesday": the rise of a women's holiday -- A cross out of bread crumbs: women's piety and impiety -- Epilogue: women and the Reformation -- Appendix A: all-women's groups -- Appendix B: Hocktide celebrations.
Includes bibliographical references (pages 299-322) and index.
In English.
JSTOR
Keywords: Parishes -- England -- History -- To 1500.; Parishes -- England -- History -- 16th century; Women -- Religious life -- England -- History -- To 1500.; Women -- Religious life -- England -- History -- 16th century; Women in church work -- England -- History -- To 1500.; Women in church work -- England -- History -- 16th century; Women -- England -- Social conditions -- 16th century; Women -- England -- History -- Middle Ages, 500-1500.; Black Death -- Social aspects -- England; Paroisses -- Angleterre -- Histoire -- 16e siècle.; Femmes -- Vie religieuse -- Angleterre -- Histoire -- 16e siècle.; Femmes -- Angleterre -- Conditions sociales -- 16e siècle.; Femmes -- Angleterre -- Histoire -- 500-1500 (Moyen Âge); Peste noire -- Aspect social -- Angleterre; HISTORY -- Medieval; Black death -- Social aspects; Parishes; Women in church work; Women -- Middle Ages; Women -- Religious life; Women -- Social conditions; England; To 1599; History